Human Resource Management in a Compartmentalized World: Whither Moral Agency? - Wilcox, Tracy (2012)
This article examines the potential for moral agency in human resource management practice. It draws on an ethnographic study of human resource managers in a global organization to provide a theorized account of situated moral agency. This account suggests that within contemporary organizations, institutional structures—particularly the structures of Anglo-American market capitalism—threaten and constrain the capacity of HR managers to exercise moral agency and hence engage in ethical behaviour. The contextualized explanation of HR management action directly addresses the question of whether HRM is inherently unethical. The discussion draws on MacIntyre’s (Philosophy 74:311–329, 1999, After Virtue: A Study in Moral Theory, Duckworth, 2000) conceptualization of moral agency within contemporary social structures. In practice, HR managers embody roles that may not be wholly compartmentalized. Alternative institutional structures can provide HR managers with a vocabulary of motives for people-centred HRM and widen the scope for the exercising of moral agency, when enacted within reflective relational spaces that provide milieus for critical questioning of logics and values. This article aims to contribute to and extend debate on whether HRM can ever be ethical, and provide a means of reconnecting business ethics with longstanding concerns in critical management studies.
Keywords: Human Resource Management; Relational spaces; Institutional Theory; Relational sociology; Moral Agency